The Evaluation of Higher Order Thinking Skills Assessment of Special Needs Education Students with Guided Inquiry Method - Imam Yuwono; Chairil Faif Pasani (Journal of ICSAR, 2018)
The competencies that have to be achieved by the Special Needs Education students of FKIP Lambung Mangkurat UniversityBanjarmasin with the enactment of curriculum based on KKNI are to develop science and technology, skills, attitude and behavior as professional education teachers. Guided inquiry study method gives the opportunity to Special Needs Education students to be actively involved in solving the problem. The aims of the research are (1) to understand about guided inquiry learning method, lecturers’ needs for HOTS level assessment instrument (antecedent phase). (2) to analyze learning implementation and students’learning difficulties (transaction phase), and (3) to know about students’ ability on HOTS level assessment (outcome phase). This research used descriptive method with Stake’s evaluation model. The research was conducted in the special needs education program of FKIP Lambung Mangkurat University Banjarmasin, with the subject of 50 students and 2 lecturers. Questionnaires were used as data collection. The results: (1) the lecturers have understood the guided inquiry method, but the learning implementation is still concentrated to the lecturers, the students are passive (2) in arranging assessment, the lecturers have not fully used the case study model to reach HOTS level, and (3) the students’ ability in completing assessment in high level (27%), moderate (42%) and low (31%). The conclusions are the lecturers have not been able to implement the real learning inquiry. It is required to review the questions together and train the students to be active so that they are able to accomplish the assessment with HOTS level.